Democracy when the people are thinking : revitalizing our politics through public deliberation - James S. Fishkin (UK Oxford University Press, 2018)
Democracy requires a connection to the 'will of the people'. What does that mean in a world of 'fake news', relentless advocacy, dialogue mostly among the like-minded, and massive spending to manipulate public opinion? What kind of opinion can the public have under such conditions? What would democracy be like if the people were really thinking in depth about the policies they must live with? If they really 'deliberated' with good information about their political choices?
Introduction -- Can the people rule? -- Making deliberation practical -- Reimagining democratic possibilities.
Includes bibliographical references and index.
Keywords: Representative government and representation; Deliberative democracy; Representative government and representation; Deliberative democracy